2019
DOI: 10.15171/apb.2019.002
|View full text |Cite
|
Sign up to set email alerts
|

Using Ketamine and Propofol for Procedural Sedation of Adults in the Emergency Department: A Systematic Review and Meta-Analysis

Abstract: Purpose: Ketamine-propofol combination (ketofol) is being used to provide a safe and effective procedural sedation (PS) in emergency department (ED) and may theoretically have beneficial effects since using lower doses of each drug may result in a reduction of the adverse events of both agents while maintaining optimal conditions for performing procedures. This systematic review was conducted to evaluate the efficacy, advantages and disadvantages of these two drugs for PS. Methods: The PRISMA statement was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 22 publications
1
35
0
2
Order By: Relevance
“…Interestingly, ketamine low dose has significantly eliminated postoperative (numeric rank score) and sore throat. Recently, the meta-analysis study of Ghojazadeh et al (2019) on the adults in the emergency department concluded that ketofol administration showed less respiratory adverse effects than propofol alone in emergency department procedural [30]. On the other hand, our results represented that age, sex, and body mass did not show any statistical differences between both sets, which matches with most of the previous studies [31,32].…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, ketamine low dose has significantly eliminated postoperative (numeric rank score) and sore throat. Recently, the meta-analysis study of Ghojazadeh et al (2019) on the adults in the emergency department concluded that ketofol administration showed less respiratory adverse effects than propofol alone in emergency department procedural [30]. On the other hand, our results represented that age, sex, and body mass did not show any statistical differences between both sets, which matches with most of the previous studies [31,32].…”
Section: Discussionsupporting
confidence: 90%
“…Psychomimetic adverse effects are known to be reduced by concomitant use of propofol [2]. Indeed, the combination has been shown to be useful in many clinical situations, with better profiles in hemodynamic stability, respiratory depression, analgesia, and recovery than each agent alone [2,5,6,7,8,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Ketofol provides reliable sedation condition using drug doses lower than typically required for each agent. The undesirable effects of ketamine such as nausea and cognitive disturbance are counterbalanced by the sedative and antiemetic effects of propofol [12]. Ketamine and propofol combination is known as safe and effective for sedation [13].…”
Section: Discussionmentioning
confidence: 99%